Spatial and Behavioural Cognition of Wayfinding System in Hospital Buildings in Terms of Oncology Patients’ Comfort - MAZURKIEWICZ Weronika; SITEK Michał (Architecture, Civil Engineering, Environment)
This paper discusses the results of a study of the quality of space in hospital buildings in the context of solutions facilitating the orientation of patients in the space of the Outpatient Clinic, in the clinic building complex of the National Institute of Oncology in Gliwice (NIO). By combining qualitative research methods with a syntactic description of the space, the aim was to record the experiences of users and define objective design guidelines for the new visual identity system. Completed research walks testing selected patient routes in the clinic space made it possible to identify decision points as nodal spaces in the wayfinding system. On the other hand, the use of the Space Syntax method allowed the identification of key areas for signage visibility and orientation in space. The proposed method can be adapted for various types of public buildings, providing a flexible framework for pre-design research and analysis. Furthermore, the results show the potential of linking qualitative research methods with simulation-based user participation and digital tools for in-depth pre-design analyses.